1997
DOI: 10.1159/000276899
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Inner-Ear Proteins in the Sera of Patients with Inner-Ear Diseases

Abstract: Sera from patients with various inner-ear diseases, especially Ménière’s disease, were investigated by Western blot against guinea pig inner-ear proteins. Of 45 patients, 24 (53%) with various inner-ear diseases had antibodies against inner-ear proteins, compared with 0 of 10 (0%) in control subjects without inner-ear diseases. Of the 10 proteins that showed a positive reaction with patient sera, the 28-kD band was unique in that it appeared only in the membranous fraction of the inner ear and was highly posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 18 publications
(37 reference statements)
1
8
1
Order By: Relevance
“…Sera obtained from their DEH patients reacted against a 68-or 35 Á/36-kDa antigen, while such a response was seen in only 3/43 normal controls. In the present study, we found that 6/8 patients had antibodies against rat inner ear proteins, a finding consistent with our previous report [8]. However, the inner ear proteins targeted by antibodies in the present patients' sera were quite different from those described in the report of Harris and Aframian [10].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Sera obtained from their DEH patients reacted against a 68-or 35 Á/36-kDa antigen, while such a response was seen in only 3/43 normal controls. In the present study, we found that 6/8 patients had antibodies against rat inner ear proteins, a finding consistent with our previous report [8]. However, the inner ear proteins targeted by antibodies in the present patients' sera were quite different from those described in the report of Harris and Aframian [10].…”
Section: Discussionsupporting
confidence: 91%
“…However, the results of these investigations, which include our own [8], are not in agreement. Damage to the inner ear causing profound hearing loss exposes the immune system to previously sequestered inner ear proteins, which may result in the production of antibodies against the inner ear.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations